Occupation/industry and risk of non-Hodgkin's lymphoma in the United States. Issue 1 (19th September 2008) - Schenk, M; Purdue, M P; Colt, J S; Hartge, P; Blair, A; Stewart, P; Cerhan, J R; De Roos, A J; Cozen, W; Severson, R K
Abstract : Aims: To identify occupations and industries associated with non-Hodgkin's lymphoma (NHL) in a large population-based, case-control study in the USA. Methods: Cases (n = 1189) of histologically confirmed malignant NHL ages 20–74 were prospectively identified in four geographic areas covered by the National Cancer Institute SEER Program. Controls (n = 982) were selected from the general population by random digit dialling (<65 years of age) and from residents listed in Medicare files (65–74 years of age). Odds ratios and 95% confidence intervals for occupations and industries were calculated by unconditional logistic regression analyses, adjusting for age, gender, ethnicity and study centre. Further analyses stratified for gender and histological subtype were also performed. Results: Risk of NHL was increased for a few occupations and industries. Several white collar occupations, with no obvious hazardous exposures, had elevated risks, including purchasing agents and buyers, religious workers, physical therapists and information clerks. Occupations with excesses that may have exposures of interest include launderers and ironers, service occupations, food/beverage preparation supervisors, hand packers and packagers, roofing and siding, leather and leather products, transportation by air, nursing and personal care facilities, and specialty outpatient clinics. Significantly decreased risks of NHL were found for a number of occupations and industries including post-secondary teachers and chemical and allied products. Conclusions: The results of this study suggest that several occupations and industries may alter the risk of NHL. Our results support previously reported increased risks among farmers, printers, medical professionals, electronic workers and leather workers. These findings should be evaluated further in larger studies that have the power to focus on specific exposures and histological subtypes of NHL.